Management of the First Patellar Dislocation: A Narrative Review - Bulgheroni, Erica; Vasso, Michele; Losco, Michele; Di Giacomo, Giovanni; Benigni, Giorgio; Bertoldi, Luciano; Schiavone Panni, Alfredo (Joints, 2019)
First patellar dislocation is a common injury of the knee, involving often adolescents and the active population. The consequences of the first episode can be various and potentially disabling. Among these, acute patellar dislocation can often result in recurrent patellar instability. Recurrent patellar instability is certainly multifactorial but depends primarily on the injury of the medial patellofemoral ligament (MPFL), the major soft-tissue stabilizer of the patella. Some classifications are extremely useful in establishing the diagnosis and therapy in patellofemoral disease, in particular in terms of instability. Among those, Henri Dejour and WARPS (weak atraumatic risky anatomy pain and subluxation)/STAID (strong traumatic anatomy normal instability and dislocation) classifications are certainly the most frequently used. There is no clear agreement on the management of the first patellar dislocation. A conservative approach seems to be the first choice in most of cases, but the presence of patellar displacement or osteochondral fractures makes surgery mandatory at the beginning. In addition, there is no clear consensus on which surgical strategy should be used to approach first dislocation, in relation to the possible variation in location of the MPFL injury, and to the eventual presence of preexisting predisposing factors for patellar instability. MPFL reconstruction may theoretically be more reliable than repair, while there is no clear evidence available that osseous abnormality should be addressed after the first episode of patellar dislocation. A narrative review was conducted to report the etiology, the diagnosis and all the possible treatment options of the first patellar dislocation. Modern classifications of the patellofemoral instability were also presented.
Keywords: patellar dislocation; medial patellofemoral ligament; medial patellofemoral reconstruction; patellar instability